Розподіл тритію в грунтових водах у районі об'єкта "Укриття" - Литвин, І.А.; Панасюк, М.І.; Левін, Г.В.; Люшня, П.А.; Сізов, М.О.; Онищенко, І.П. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
За останні роки спостерігається значне (5 - 12 разів) зниження об'ємних активностей тритію в ґрунтових водах, що пройшли шлях фільтрації під об'єктом «Укриття». Показано, що зниження концентрацій тритію відбувається через зміну напрямку руху підземних вод під впливом зниження рівня води у водоймі-охолоджувачі. За последние годы наблюдается значительное (5 - 12 раз) снижение объемных активностей трития в грунтовых водах, прошедших путь фильтрации под объектом «Укрытие» Показано, что снижение концентраций трития происходит из-за изменения направления движения подземных вод под воздействием снижения уровня воды в пруду-охладителе. We chose tritium as an indicator of the supply and distribution of radioactive water from the water accumulations of the "Ukryttya" object into the surrounding underground environment. Since 1997, the maximum volumetric activity of tritium in blocky waters was 660 – 23194 Bq/l. In groundwaters, the highest concentrations of tritium reached values of 1105 – 8175 Bq/l. Over the past few years there has been a significant (5-12 times) decrease in volumetric activity of tritium in groundwater, which filtered under the object "Ukryttya". The article shows that tritium concentrations decrease as a result of changing of the groundwater flow direction, which changes under the influence of the water level in the pond-cooler.